The Effect of Green Transformational Leadership and Work Motivation on Employee Performance at PT Mega Asia Global - Tekni Megaster (International Journal of Business and Applied Economics, 2023)
This study aims to determine the effect of green transformational leadership and employee performance on employee performance. This study uses a probability sampling technique with a random sampling technique from the population regardless of the strata in the population. The results of the study at a significance level of 5% showed that: (1) green transformational leadership had a positive and significant effect on employee performance, as evidenced by the value of tcount > ttable (9,119 > 1,991) with a significance value of 0.000 less than 0.05 (0.000 < 0 0.05), (2) work motivation has a positive and significant effect on employee performance, as evidenced by the value of tcount > ttable (7,997 > 1,991) with a significance value of 0.000 less than 0.05 (0.000 < 0.05) and (3) green transformational leadership and work motivation together have a positive and significant effect on employee performance, as evidenced by the results of the Fcount > Ftable (45.409 > 3.12) with a significance value of 0.000 less than 0.05 (0.000 < 0.05) green transformational leadership and work motivation affect employee job satisfaction 60.0% while the remaining 40.0% is influenced by other factors that are not included in the research model. multiple regression equation value Y=2,942 + 0.470X1 + 0.416 X2 .